2017
DOI: 10.3390/rs9050497
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Decadal Surface Water Dynamics in North American Tundra

Abstract: Abstract:Over the last several decades, warming in the Arctic has outpaced the already impressive increases in global mean temperatures. The impact of these increases in temperature has been observed in a multitude of ecological changes in North American tundra including changes in vegetative cover, depth of active layer, and surface water extent. The low topographic relief and continuous permafrost create an ideal environment for the formation of small water bodies-a definitive feature of tundra surface. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
46
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(55 citation statements)
references
References 49 publications
(67 reference statements)
1
46
0
2
Order By: Relevance
“…Collectively, our results suggest that some component of the browning trends in boreal forests that are not a direct result of land use, fire, or other landscape disturbances Carroll & Loboda, 2017;Goetz et al, 2005;Ju & Masek, 2016;Nitze et al, 2017;Raynolds & Walker, 2016) may be related to droughtand insect-induced tree mortality. We highlight the particular vulnerability of the interior southern boreal, where widespread browning trends (Guay et al, 2014;Ju & Masek, 2016;Sulla-Menashe, Woodcock, & Friedl, 2018) are coupled to recent mortality events, and projections suggest continued drought and potential transitions to open forest or grassland (Abis & Brovkin, 2017;Hogg & Hurdle, 1995;Lenihan & Neilson, 1995;Worrall et al, 2013).…”
Section: Discussionmentioning
confidence: 72%
“…Collectively, our results suggest that some component of the browning trends in boreal forests that are not a direct result of land use, fire, or other landscape disturbances Carroll & Loboda, 2017;Goetz et al, 2005;Ju & Masek, 2016;Nitze et al, 2017;Raynolds & Walker, 2016) may be related to droughtand insect-induced tree mortality. We highlight the particular vulnerability of the interior southern boreal, where widespread browning trends (Guay et al, 2014;Ju & Masek, 2016;Sulla-Menashe, Woodcock, & Friedl, 2018) are coupled to recent mortality events, and projections suggest continued drought and potential transitions to open forest or grassland (Abis & Brovkin, 2017;Hogg & Hurdle, 1995;Lenihan & Neilson, 1995;Worrall et al, 2013).…”
Section: Discussionmentioning
confidence: 72%
“…Most studies of surface water extent change are performed using a thresholding method to classify an image pair (or a few dates) to get the difference in water extent between those dates (Hinkel et al 2007, Smith et al 2005, Yoshikawa and Hinzman 2003. However, those methods that pick a difference between two arbitrarily selected points in time are likely plagued with considerable uncertainty due to a naturally large inter-annual variability of water extent as demonstrated in Carroll and Loboda (2017). Better approaches focus on multi-temporal assessment of long-term trends in surface water change.…”
Section: Introductionmentioning
confidence: 99%
“…Lastly a regional study in northern Nunavut (Canada) used the full time series of Landsat to generate annual maps of the nominal surface water extent. These maps were converted to polygons and used to generate a trend in areal extent for each water body (Carroll and Loboda 2017). Unlike the methods from Carroll and Loboda 2017 and Pekel et al 2016, the method from Nitze et al 2017 produces a single output map that shows the classification with change as a class rather than annual maps that are used in a secondary analysis for change.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Images of satellite sensing have been applied extensively to analyze the changes of surface water in the Arctic from the local scale [1][2][3][4][5]. Smith et al [3] reported that lakes in Siberia are disappearing.…”
Section: Introductionmentioning
confidence: 99%